2009
DOI: 10.1002/hep.23322
|View full text |Cite
|
Sign up to set email alerts
|

Lack of interleukin-6/glycoprotein 130/signal transducers and activators of transcription-3 signaling in hepatocytes predisposes to liver steatosis and injury in mice

Abstract: A deregulated cytokine balance is involved in triggering the sequence from steatosis to nonalcoholic steatohepatitis, ultimately leading to liver fibrosis and cancer. To better define the role of proinflammatory interleukin-6 (IL-6)-type cytokines in hepatocytes we investigated the role of IL-6 and its shared receptor, glycoprotein 130 (gp130), in a mouse model of steatohepatitis. IL-6 ؊/؊ mice were fed a choline-deficient, ethionine-supplemented (CDE) diet. Conditional gp130 knockout and knockin mice were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 23 publications
3
55
1
Order By: Relevance
“…We speculate that, although an excess of IL-6 may exert an effect as a mediator of inflammation in human and mouse NASH, in some experimental models with severely suppressed IL-6-STAT3 signaling, such as STAT3 À/À or GP130 À/À mice, IL-6 may have a hepato-protective role against various types of liver injury, including steatohepatitis, as we have demonstrated in this study. 33,34 We found here that MR16-1 treatment did not exacerbate hepatic steatosis (Figure 4a-d) and the expression of lipogenic genes was not altered (data not shown), despite inhibited IL-6 signaling. However, although MR16-1 treatment decreased plasma FFA levels with increased hepatic lipogenic fed wild-type mice (Supplementary Figure 2D, E, 17 ), these were greatly increased in MCD diet-fed db/db mice.…”
Section: Discussionmentioning
confidence: 74%
“…We speculate that, although an excess of IL-6 may exert an effect as a mediator of inflammation in human and mouse NASH, in some experimental models with severely suppressed IL-6-STAT3 signaling, such as STAT3 À/À or GP130 À/À mice, IL-6 may have a hepato-protective role against various types of liver injury, including steatohepatitis, as we have demonstrated in this study. 33,34 We found here that MR16-1 treatment did not exacerbate hepatic steatosis (Figure 4a-d) and the expression of lipogenic genes was not altered (data not shown), despite inhibited IL-6 signaling. However, although MR16-1 treatment decreased plasma FFA levels with increased hepatic lipogenic fed wild-type mice (Supplementary Figure 2D, E, 17 ), these were greatly increased in MCD diet-fed db/db mice.…”
Section: Discussionmentioning
confidence: 74%
“…IL-6 alleviates liver steatosis 63 and IL-6 À/À mice develop mature-onset obesity and are prone to hepatic steatosis and metabolic alterations. 64,65 According to the regulatory role of CD154 on IL-6 expression, we found that CD154KO mice showed impaired induction of IL-6 following the olive oil-rich diet as shown by a reduced induction of plasma IL-6 levels and liver IL-6 mRNA (Supporting Fig. 9A,B).…”
Section: Discussionmentioning
confidence: 93%
“…In a recent report, adenovirus-mediated liverspecific OB-Rb overexpression has been shown to activate AMPK pathway to reduce lipid synthesis and promote lipid oxidation and eventually resulted in apparent amelioration of hepatosteatosis in mice under HF conditions (Yoshino et al 2014). Meanwhile, a number of studies showed that deficiency in STAT3, a major signaling pathway downstream of OB-Rb, or its upstream gp130 in hepatocytes exacerbates fatty liver induced by a cholinedeficient, ethionine-supplemented diet (Kroy et al 2010), alcohol-containing diet (Horiguchi et al 2008) or highfat diet (Inoue et al 2004), whereas overexpression of constitutively activated STAT3 ameliorates high-fat dietinduced fatty liver via inhibition of SREBP-1c (Inoue et al 2004, Kinoshita et al 2008. Future studies are thus required to clarify the physiological functions of AMPK and STAT3 pathways downstream of leptin/OB-Rb in mediating the antisteatotic effects of metformin in liver.…”
Section: Discussionmentioning
confidence: 99%